A New Strategy to Build a High‐Performance P′2‐Type Cathode Material through Titanium Doping for Sodium‐Ion Batteries. (8th May 2019) - Park, Yun Ji; Choi, Ji Ung; Jo, Jae Hyeon; Jo, Chang‐Heum; Kim, Jongsoon; Myung, Seung‐Taek
Abstract: Herein, Ti 4+ in P′2‐Na0.67 [(Mn0.78 Fe0.22 )0.9 Ti0.1 ]O2 is proposed as a new strategy for optimization of Mn‐based cathode materials for sodium‐ion batteries, which enables a single phase reaction during de‐/sodiation. The approach is to utilize the stronger Ti–O bond in the transition metal layers that can suppress the movements of Mn–O and Fe–O by sharing the oxygen with Ti by the sequence of Mn–O–Ti–O–Fe. It delivers a discharge capacity of ≈180 mAh g −1 over 200 cycles (86% retention), with S‐shaped smooth charge–discharge curves associated with a small volume change during cycling. The single phase reaction with a small volume change is further confirmed by operando synchrotron X‐ray diffraction. The low activation barrier energy of ≈541 meV for Na + diffusion is predicted using first‐principles calculations. As a result, Na0.67 [(Mn0.78 Fe0.22 )0.9 Ti0.1 ]O2 can deliver a high reversible capacity of ≈153 mAh g −1 even at 5C (1.3 A g −1 ), which corresponds to ≈85% of the capacity at 0.1C (26 mA g −1 ). The nature of the sodium storage mechanism governing the ultrahigh electrode performance in a full cell with a hard carbon anode is elucidated, revealing the excellent cyclability and good retention (≈80%) for 500 cycles (111 mAh g −1 ) at 5C (1.3 A g −1 ). Abstract : The substitution of Mn with Fe 3+ and Ti 4+ in P′2‐type Na0.67 [(Mn0.78 Fe0.22 )0.9 Ti0.1 ]O2 leads to the suppression of phase transitions with an increased average Mn oxidation state. Therefore, it delivers high reversible capacity during cycling with a small volume change. Above all, it shows excellent high rate capability, accompanied by low activation barrier energy of ≈541 meV for Na + diffusion.